Hypothesis: Potentially Systemic Impacts of Elevated CO2 on the Human Proteome and Health - Duarte, Carlos M.; Jaremko, Łukasz; Jaremko, Mariusz (Frontiers in Public Health, 2020)
Uniform CO2 during human evolution (180 to 280 ppm) resulted, because of the role of the CO2-bicarbonate buffer in regulating pH, in rather constant pH (7.35 to 7.45) in human fluids, cells and tissues, determining, in turn, the narrow pH range for optimal functioning of the human proteome. Herein, we hypothesize that chronic exposure to elevated pCO2 with increasing atmospheric CO2 (>400 ppm), and extended time spent in confined, crowded indoor atmospheres (pCO2 up to 5,000 ppm) with urban lifestyles, may be an important, largely overlooked driver of change in human proteome performance. The reduced pH (downregulated from 0.1 to 0.4 units below the optimum pH) of extant humans chronically exposed to elevated CO2 is likely to lead to proteome malfunction. This malfunction is due to protein misfolding, aggregation, charge distribution, and altered interaction with other molecules (e.g., nucleic acids, metals, proteins, and drugs). Such alterations would have systemic effects that help explain the prevalence of syndromes (obesity, diabetes, respiratory diseases, osteoporosis, cancer, and neurological disorders) characteristic of the modern lifestyle. Chronic exposure to elevated CO2 poses risks to human health that are too serious to be ignored and require testing with fit-for-purpose equipment and protocols along with indoor carbon capture technologies to bring CO2 levels down to approach levels (180–280 ppm) under which the human proteome evolved.